The Reception of Choi Siwon’s Transnational Star Image by Indonesian ELF Fandom: An Encoding–Decoding Analysis - Basar Ananta Farrel Silitonga; Aprilianti Pratiwi (INJECT (Interdisciplinary Journal of Communication), 2025)
This study aims to analyze the synergy between the Korean entertainment industry’s Star System and fandom reception in shaping and reinforcing the global image of Choi Siwon as a transnational figure within cross-border marketing practices. Using a descriptive qualitative approach, data were collected through in-depth interviews with three informants from the ELF fandom and document studies of promotional materials, media coverage, and commercial data related to brands collaborating with Choi Siwon. The analysis employs Stuart Hall’s Encoding–Decoding framework to trace how audiences interpret the industry-constructed image. Findings reveal that Siwon’s persona—combining roles as an idol, actor, and philanthropist—is the result of a systematic Star System that produces a stable and marketable public identity. ELF fandom generally decodes this image dominantly, interpreting Siwon as charismatic, professional, and morally grounded. This interpretation fosters consumption loyalty, demonstrated by increased engagement and product sales endorsed by Siwon, including the Mie Sedaap campaign, which recorded a significant rise in the Indonesian market. These findings confirm that the synergy between the Star System and fandom reception forms an effective global marketing mechanism through celebrity image reinforcement and active audience participation.